ENVIRONMENTAL PROBLEMS OF SUSTAINABLE DEVELOPMENT AND IMPROVEMENT OF URBAN AREAS AND WAYS OF THEIR DECISION - A. Z. Al-Fahad (Вестник университета)
In this article features of influence of an ecological factor of development of urban areas on formation of improvement of the cities, the most expedient ways of providing a favorable ecological situation of urban areas, major factors interfering development of improvement of urban areas and offers of decisions for achievement of the favorable ecological environment in the cities are investigated.